The Rhetoric of Popular Science Texts. Scientific American Magazine as a Typical Example - Lichański, Jakub Z. (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The aim of the study is to describe the relationship between rhetoric and popular science texts. Scientific American magazine is taken as an example. In conclusion, the author suggests that the rhetoric of popular science texts rests on the presentation of a problem, avoiding controversy in the presentation of research issues, avoiding modal forms and the use of multiple elements of visual rhetoric. This article contains brief historical information about the development of the magazine Scientific American.